Research of the adsorption of a methylene blue enterosorbents of various nature - Lishai, Nastassia V.; Savitskaya, Tatsiana A.; Tsyhankova, Nadzeia G.; Hrynshpan, Dzmitry D.; Chen, Jun (Journal of the Belarusian State University. Chemistry, 2021)
The results of the adsorption study of methylene blue dye as the low molecular weight toxins marker from its aqueous solutions by carbon, silicon and polymer enterosorbents are presented. It has been shown that the activated carbons modification by water-soluble cellulose polyelectrolyte makes it possible to increase their adsorption capacity. The applicability of Langmuir, Freundlich, Temkin and Redlich – Peterson adsorption models for the approximation of experimental adsorption isotherms of methylene blue on the enterosorbents has been estimated. It has been established that the three-parameter Redlich – Peterson equation describes this process better than others. This was evident from the comparison of the regression coefficients, constants and parameters values of these equations.